Acupressure therapy to reduce the intensity of smoking habits - Suhariyanti, Enik; Aini, Nora Nur; Ardianingrum, Nadia (Community Empowerment, 2021)
Efforts to improve a healthy lifestyle are very important, one of them is to stop smoking. The way to stop smoking can be through acupressure complementary therapy training and counseling on smoking health risks. The purpose of this activity is to increase public awareness and knowledge regarding the smoking health risks and acupressure therapy in order to reduce the desire to smoke for residents in the Bandung Village, Mertoyudan District, Magelang Regency. This activity involves the participation of the local community so that they can realize the importance of reducing smoking habits and the impact of smoking. The method used was counseling on the smoking health risks and acupressure training. The results of the activity showed that the residents were enthusiastic in participating in the activity and were able to apply acupressure therapy in their daily lives to stop smoking.